Mobile Forensic Investigation of Fake News Cases on Instagram Applications with Digital Forensics Research Workshop Framework - Riadi, Imam; Herman, Herman; Rafiq, Irhash Ainur (International Journal of Artificial Intelligence Research, 2022)
The number of digital crimes or cybercrimes today continues to increase every year, and lately a lot of it happens on social media like Instagram. The social behavior of today's people who communicate more through social media encourages the perpetrators of these digital crimes. Instagram is a social media that is often found content that contains elements of pornography, hoax news, hate speech, etc. This research is aimed at processing digital evidence of cases of the spread of hoax news on the Instagram application. This research follows the framework of the Digital Forensics Research Workshop (DFRWS) with six stages, namely identification, preservation, collection, examination, analysis, and presentation. The process of obtaining digital evidence is assisted by the application of Axiom Magnet and Cellebrite UFED. Digital evidence sought from the smartphone device of the suspected hoax news disseminator seized following the case scenario consists of 8 variables in the form of accounts, emails, images, videos, URLs, times, IP address, and location. The results of this research with the help of the application of Magnet Axiom digital proof obtained 87.5% and the Cellebrite UFED application of 68.75%. The results of this study show that Magnet Axiom has better performance than MOBILedit Forensics.